Forest Service Research Data Archive
DOI: 10.2737/rds-2005-0002
|View full text |Cite
|
Sign up to set email alerts
|

Data product containing campsite assessments for "Effectiveness of a Confinement Strategy in Reducing Pack Stock Impacts at Campsites in the Selway-Bitterroot Wilderness, Idaho"

Abstract: In 1993, a management program was initiated in the Seven Lakes Basin in the Selway-Bitterroot Wilderness to bring high levels of campsite impact into compliance with management standards. The core of the strategy involved confining use, particularly by stock groups, and restoring certain campsites and portions of campsites. In just five years, campsite impacts were reduced substantially. Disturbed and bare area decreased on campsites, as did tree scarring and mineral soil exposure. Vegetation cover increased. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…They are more consistent with the campsite containment programme evaluated by Spildie et al (2000), which reported a 37% reduction in aggregate disturbed area and 43% reduction in exposed soil. The success of site closures in this study can be attributed to the persistent rehabilitation efforts of park managers and the recovery of many sites through natural causes such as downed trees and fallen leaves.…”
Section: Closure and Rehabilitation Successsupporting
confidence: 76%
See 1 more Smart Citation
“…They are more consistent with the campsite containment programme evaluated by Spildie et al (2000), which reported a 37% reduction in aggregate disturbed area and 43% reduction in exposed soil. The success of site closures in this study can be attributed to the persistent rehabilitation efforts of park managers and the recovery of many sites through natural causes such as downed trees and fallen leaves.…”
Section: Closure and Rehabilitation Successsupporting
confidence: 76%
“…These actions contributed to a 50% reduction in the cumulative area of disturbance, despite slight increases in degradation on campsites left open to visitors. Similarly, a camping confinement strategy that included designating sites for stock users, site closure and restoration work substantially reduced resource impacts over a five-year period in wilderness campsites in Idaho (Spildie et al 2000). In contrast, using pre-and post-policy campsite condition assessments in two Oregon wilderness areas, Hall (2001) concluded that a designated-site management policy yielded mixed success.…”
Section: Introductionmentioning
confidence: 99%
“…In the Selway-Biterroot Wilderness of Idaho, a spatial containment strategy designated a reduced number of stock containment areas, coupled with the closure and intensive restoration of other sites to stock use. In ®ve years, the areal extent of disturbance was reduced by 37 percent and bare soil was reduced more than 40 percent (Spildie et al, 2000). Camping disturbance at Delaware Water Gap National Recreation Area in Pennsylvania and New Jersey was reduced 50 percent over a ®ve-year period, primarily through the designation of individual campsites and installation of permanently ®xed ®re grates (Marion, 1995).…”
Section: Literature Reviewmentioning
confidence: 89%
“…This includes establishing minimum acceptable levels of change in productivity and/or vegetation structure (e.g. 10%) as suggested for mountain meadows with recreational pack animals in North America (Spildie et al, 2000;Cole et al, 2004). To meet their conservation criteria, monitoring programs and management strategies including deferred grazing, rotating grazing areas between years, use of weed-free fodder for livestock, or establishing limits on the number and animal nights per meadow could be implemented (Moore et al, 2000).…”
Section: Discussionmentioning
confidence: 99%